Justification of methods for regulation the salt regime of irrigated soils in Uzbekistan under current conditions - Shirokova Yulia; Paluashova Gauharay; Sadiev Farkhod; Kodirov Dilshod; Urazkeldiev Abdivohid (E3S Web of Conferences, 2023)
Foreign approaches to maintaining a favorable salt regime of soils are analyzed. On the basis of experimental studies, a change in the water-physical properties of the soil during deep loosening and an increase in salt leaching during leaching and vegetation irrigation using the Biosolvent preparation were established. Based on the analysis of the leaching results, the optimal technologies and norms for leaching saline soils have been established.